Efficacy and Safety of MED2005, a Topical Glyceryl Trinitrate Formulation, in the Treatment of Erectile Dysfunction: A Randomized Crossover Study. Issue 2 (3rd January 2018) - Ralph, David J.; Eardley, Ian; Taubel, Jorg; Terrill, Paul; Holland, Tim
Abstract: Background: Current treatments for erectile dysfunction (ED) have some limitations. Aim: This study evaluated the efficacy and tolerability of MED2005, a 0.2% glyceryl trinitrate topical gel, formulated into an enhanced absorption topical delivery system (DermaSys), administered on demand, in the treatment of ED. Methods: This randomized, double-blinded, placebo-controlled, phase II crossover trial involved 232 men with ED (231 treated, 230 assessed for efficacy) and their partners. After a 4-week run-in period, patients were randomized to 1 of 2 treatment sequences, MED2005-placebo or placebo-MED2005. Each treatment was given for 4 weeks, separated by a 1-week washout interval. Efficacy was assessed by the International Index of Erectile Function (IIEF), the Sexual Encounter Profile, a Global Assessment Questionnaire (GAQ), and specific questions about the onset and offset of action and treatment preferences (patients and partners). Outcomes: The primary outcome measure was the IIEF erectile function domain (IIEF-EF) score. Other efficacy assessments were secondary outcomes. Results: The mean baseline IIEF-EF score was 17.1 (SD = 5.7), and this increased to 19.6 (SD = 7.5) after MED2005 treatment and 18.5 (SD = 6.7) after placebo ( P  = .0132). Overall, 23.1% of patients showed a clinically relevant (≥4-point) increase in IIEF-EF scores after treatment with MED2005 only compared with 14.5% who responded after MED2005 and placebo, 14.0% who responded after placebo only, and 48.4% who did not respond after either treatment ( P  = .0272). MED2005 also was associated with significant improvements compared with placebo in the other IIEF domains, and this was consistent with patients' and partners' responses to the GAQ. For all assessments, significant effects of MED2005 were seen primarily in patients with mild ED. The start of erection was noticed within 5 and 10 minutes in 44.2% and 69.5%, respectively, of all intercourse attempts with MED2005. Patients and partners showed significant preferences for MED2005 over placebo. The most commonly reported adverse events during MED2005 treatment were headache (patients, n = 18 [7.9%]; partners, n = 3 [1.3%]) and nasopharyngitis (patients, n = 13 [5.7%]; partners, n = 2 [0.9%]). Clinical Implications: These findings suggest that topical glyceryl trinitrate could be a useful treatment option in ED. Strengths and Limitations: Strengths of this study include the use of a validated outcome measure. Limitations include the use of only 1 dosage. Conclusion: Further studies are warranted to investigate the efficacy of topical glyceryl trinitrate to include higher doses, thereby improving clinical significance, especially in cases of moderate and severe ED.